Economía y defensa nacional : algunas reflexiones - Giovaneli, Jorge A. (1956)
Giovaneli, J. A. (1956). Economía y defensa nacional : algunas reflexiones. Revista de la Escuela Superior de Guerra. 34 (321), 5-23.